2023
DOI: 10.1021/acs.est.3c02340
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Ozone-Dependent Emissions of Volatile Organic Compounds from the Human Body

Yuekun Qu,
Ziwei Zou,
Charles J. Weschler
et al.

Abstract: Ozone reactions on human body surfaces produce volatile organic compounds (VOCs) that influence indoor air quality. However, the dependence of VOC emissions on the ozone concentration has received limited attention. In this study, we conducted 36 sets of single-person chamber experiments with three volunteers exposed to ozone concentrations ranging from 0 to 32 ppb. Emission fluxes from human body surfaces were measured for 11 targeted skin-oil oxidation products. For the majority of these products, the emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
3
12
0
Order By: Relevance
“…Most of the Yield gas values in Table are dominated by products of the ozone/skin oil chemistry: 16 “passengers” in a 28 m 3 simulated aircraft cabin, 2 occupants in a sparsely furnished 28 m 3 simulated office, 4 volunteers in a 22 m 3 chamber, and a single occupant in a very small (1.5 m 3 ) chamber . The major products contributing to Yield gas in these studies were acetone, 6-MHO, 4-OPA, decanal, nonanal, nonenal, and acetic acid.…”
Section: Quantitative Relationships Describing Indoor Ozone Lossmentioning
confidence: 81%
See 3 more Smart Citations
“…Most of the Yield gas values in Table are dominated by products of the ozone/skin oil chemistry: 16 “passengers” in a 28 m 3 simulated aircraft cabin, 2 occupants in a sparsely furnished 28 m 3 simulated office, 4 volunteers in a 22 m 3 chamber, and a single occupant in a very small (1.5 m 3 ) chamber . The major products contributing to Yield gas in these studies were acetone, 6-MHO, 4-OPA, decanal, nonanal, nonenal, and acetic acid.…”
Section: Quantitative Relationships Describing Indoor Ozone Lossmentioning
confidence: 81%
“…Liu et al 30 found that in measurements made with a PTR-MS in a normally occupied residence over an 8-week period, the concentrations of several ozone-derived products scaled in a roughly linear fashion with the indoor ozone concentration (See Figure 3 of the cited paper.). In a chamber study of products resulting from ozone reactions with human surfaces, Qu et al 47 observed that for most volatile products resulting from indoor ozone reactions, there was a linear relationship between emission rates and ozone concentration. Byproduct concentrations would be proportional to byproduct emission rates if byproduct loss from indoor air occurs only by ventilation and there are no other meaningful emission sources, including outdoor air.…”
Section: ■ Quantitative Relationships Describing Indoor Ozone Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…Even for these two reactions, some parameters have not been measured directly. In this study we followed the approach used in our recent chamber study for parametrization and represented the reactions as follows 6 ‐MHO + normalO 3 k 6 MHO 0.3 .25em acetone + 0.8 .25em 4 ‐OPA GA + normalO 3 k GA 0.15 .25em 6 ‐MHO + 0.4 .25em 4 ‐OPA + 0.15 .25em acetone + 0.4 .25em 4 ‐MON where k 6‑MHO and k GA are the ozone reaction rate coefficient with 6-MHO and geranyl acetone, respectively. They were assigned values of 0.035 and 0.070 ppb –1 h –1 .…”
Section: Methodsmentioning
confidence: 99%